2017
DOI: 10.1091/mbc.e16-10-0712
|View full text |Cite
|
Sign up to set email alerts
|

Osm1 facilitates the transfer of electrons from Erv1 to fumarate in the redox-regulated import pathway in the mitochondrial intermembrane space

Abstract: Osm1 transfers electrons from fumarate to succinate and functions with Mia40 and Erv1 in the redox-regulated import pathway for proteins that form disulfide bonds in the mitochondrial intermembrane space. Expression of Osm1 and cytochrome c is reciprocally regulated, indicating that the cell has strategies to coordinate expression of terminal electron acceptors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 76 publications
0
29
0
Order By: Relevance
“…Both of these peroxidase enzymes were shown to interact with components of the MIA machinery directly, thus they can scavenge hydrogen peroxide produced from the MIA pathway effectively. Moreover, a recent study showed that yeast Erv1 can also transfer electrons to the IMS localised fumarate reductase Osm1, and via Osm1 transfer electrons to fumarate under both aerobic and anaerobic conditions . Thus, yeast can exploit diverse electron acceptors for MIA pathway in the IMS, with at least three electron acceptors, oxygen, cytochrome c and Osm1/fumarate, have been identified.…”
Section: Discussionmentioning
confidence: 99%
“…Both of these peroxidase enzymes were shown to interact with components of the MIA machinery directly, thus they can scavenge hydrogen peroxide produced from the MIA pathway effectively. Moreover, a recent study showed that yeast Erv1 can also transfer electrons to the IMS localised fumarate reductase Osm1, and via Osm1 transfer electrons to fumarate under both aerobic and anaerobic conditions . Thus, yeast can exploit diverse electron acceptors for MIA pathway in the IMS, with at least three electron acceptors, oxygen, cytochrome c and Osm1/fumarate, have been identified.…”
Section: Discussionmentioning
confidence: 99%
“…This is an important difference as the cytochrome c pathway ends up with the production of H 2 O after a relay by cytochrome oxidase whereas a direct reaction with oxygen implies H 2 O 2 production. In yeast grown in anaerobic conditions, electrons can be transferred to the Osm1/fumarate couple in the mitochondrial intermembrane space (Neal et al ., ).…”
Section: The Disulfide Relay In the Mitochondrial Intermembrane Spacementioning
confidence: 99%
“…Erv1 can either directly reduce oxygen to hydrogen peroxide or use cytochrome c as an electron acceptor (Figure 3 ). Alternatively, it can interact with the fumarate reductase Osm1 in order to get re-oxidized under anaerobic conditions (Neal et al, 2017 ).…”
Section: The Mitochondrial Disulfide Relaymentioning
confidence: 99%